Effect of glucagon-like peptide-1 receptor agonists on vascular risk factors among adults with type 2 diabetes and established atherosclerotic cardiovascular disease - Aaron King; Xi Tan; Neil Dhopeshwarkar; Rhonda Bohn; Katherine Dea; Charles E. Leonard; Adam de Havenon (American Journal of Preventive Cardiology)
Introduction: Limited data exist on the cardiovascular effectiveness of once-weekly (OW) glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in real-world practice. Methods: We assessed the OW GLP-1 RA effects on vascular risk factors in adults with type 2 diabetes and atherosclerotic cardiovascular disease using data from a large-scale US electronic health record database (index date = first prescription of OW GLP-1 RA). Exploratory analyses were performed on patients newly initiating OW GLP-1 RAs with semaglutide, OW GLP-1 RAs without semaglutide, and semaglutide. Changes in vascular risk factors were evaluated by comparing mean measures between the 12-month pre- and post-index periods. Analyses were conducted for all three cohorts and subpopulations including stratified by tercile of baseline vascular risk factor value. Results: In the final cohorts ([1] OW GLP-1 RA including semaglutide: n = 20,084; [2] OW GLP-1 RA excluding semaglutide: n = 16,894; [3] semaglutide: n = 3,435), significant mean reductions (P < 0.001) were observed from baseline to post-index in hemoglobin A1c (%, [1] -1.1; [2] -1.1; [3] -1.2), low-density lipoprotein cholesterol (mg/dL, [1] -6.4; [2] -6.4; [3] -6.9), total cholesterol (mg/dL, [1] -11.0; [2] -11.1; [3] -10.7), triglycerides (mg/dL, [1] -31.8; [2] -31.4; [3] -33.1), systolic blood pressure (mmHg, [1] -1.5; [2] -1.2; [3] -3.1), body weight (kg, [1] -2.7; [2] -2.4; [3] -4.3) and body mass index (kg/m2; [1] -0.9; [2] -0.8; [3] -1.4). Largest reductions were observed in the top tercile. Conclusion: Our data suggest GLP-1 RAs are associated with significant reductions in key vascular risk factors in real-world practice.